The rights of contriver of the agricultural varieties and his civil protection according to the Iraqi Agricultural Varieties Registration, Accreditation and Protection Law No. 51 of 2012 - prof. Dr.. Amal Kazem Saud; Assistant Professor Dr. Muhammad Ali Sahib Hassan (The college of law and political science journal, 2023)
.